Migraine and Two-Pore-Domain Potassium Channels. (June 2021) - Verkest, Clément; Häfner, Stephanie; Ávalos Prado, Pablo; Baron, Anne; Sandoz, Guillaume
Migraine is a common, disabling neurological disorder with a genetic, environmental, and hormonal component with an annual prevalence estimated at 15%. It is characterized by attacks of severe, usually unilateral and throbbing headache, and can be accompanied by nausea, vomiting, and photophobia. Migraine is clinically divided into two main subtypes: migraine with aura, when it is preceded by transient neurological disturbances due to cortical spreading depression (CSD), and migraine without aura. Activation and sensitization of trigeminal sensory neurons, leading to the release of pro-inflammatory peptides, is likely a key component in headache pain initiation and transmission in migraine. In the present review, we will focus on the function of two-pore-domain potassium (K2P ) channels, which control trigeminal sensory neuron excitability and their potential interest for developing new drugs to treat migraine.